American Mastodon - Clay, Kathryn (North Mankato, Minnesota : Capstone Press, 2018)
"The American mastodon thundered through the Ice Age. With its powerful tusks and large size, few predators challenged this prehistoric beast. Readers learn about this mighty plant eater from engaging text and bold illustrations reviewed by Smithsonian experts."--
Ages 5-9.
105672
Keywords: Mastodons -- Juvenile literature; Mammals, Fossil -- Juvenile literature; Prehistoric animals; Juvenile works